The effect of Philaenus spumarius feeding on the endophytic fungi community of Coleostephus myconis and its possible applicability in the insect biocontrol - Cameirão, Cristina (2019)
Philaenus spumarius was recently confirmed as the European vector for the ongoing Xylella fastidiosa outbreak in the olive orchards of Southern Italy. In the northeast region of Portugal, P. spumarius is widespread and common in olive groves. In these groves was observed that their nymphs feed preferentially on the weed Coleostephus myconis, displaying in the same time period and area different levels of infestation. This work aims to assess the correlation between the fungal endophytic communities inhabiting C. myconis with the feeding preference of P. spumarius. Fungi were isolated from stems, leaves and inflorescences of plants with three levels of P. spumarius infestation (no infestation, moderate and high infestation), collected in an olive grove located in Mirandela. The fungal isolates were further identified by sequencing the ITS region of rDNA and the partial tef1. A total of 138 OTUs belonging to 37 genera were isolated, being Alternaria, Valsa, Cladosporium and Chalastospora the most abundant genera. An increase in overall endophytic fungal abundance and richness was observed across infestation levels, in particular of isolates belonging to Chalastospora and Cladosporium. In contrast, Biscogniauxia, Chaetomium and Stemphylium, decreased across the levels of infestation. Differences in fungal composition between non-infested and infested plants were particularly observed in stems, where the P. spumarius foam nests are present. Some genera were exclusively found either in non-infested or in infested plants. Our survey provides fungal candidates to further evaluate their role in the repellency/attraction of P. spumarius in order to develop new management tools against this insect.